Agripreneurship incubation and accelerator insights and lessons from Wennovation Hub (Nigeria) - Odetayo, Wole (Technical Centre for Agricultural and Rural Cooperation, 2018)
Wole Odetayo, the Executive Director of Wennovation Hub in Nigeria shares his experience on incubation and acceleration.